Uji Efektivitas Jamu Kunyit (Curcuma domestica) dan Jamu Jahe Merah (Zingiber officinale var. Rubrum) sebagai Antimikroba Bakteri Salmonella (Salmonella typhi) dalam Upaya Penyusunan Petunjuk Praktikum Mikrobiologi - Diyan Islami; Iwan Doddy Dharmawibawa; Sucika Armiani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Jamu is a traditional medicinal drink used by Indonesian people since ancient times. Herbal medicine is made from spices used in the form of leaves, stems, flowers, fruit, bark, and rhizomes. Herbal medicine that is often used as traditional medicine is herbal medicine from turmeric and red ginger. The part of turmeric (Curcuma domestica) and red ginger (Zingiber officinale var. Rubrum) that can be used as herbal medicine is the rhizome. This type of research is a descriptive study and only proves antibacterial activity by measuring the diameter of the inhibition zone of the activity of turmeric and ginger herbs in inhibiting the growth process of Salmonella typhi. The method used is the well method, the research is an experimental study, the population is turmeric herbs and red ginger herbs. The data analysis technique used is descriptive and only calculates the inhibition zone fomed by the large inhibition zone formula, the concentrations used in this study were 100%, 75%, 50%, and 25%. The negative control used was distilled water and the positive control used was amoxicillin. Jamu with a concentration variation of 100% formed the largest inhibition zone,the combination of Jamu Turmeric and Jamu Red Ginger formed an inhibition zone with an average of 4.6 mm, secondly, while Jamu Turmeric formed an average inhibition zone of 2.83 mm and Jamu Ginger formed an inhibition zone with an average 2.33 mm average. Herbal turmeric and red ginger herbs can inhibit the growth of Salmonella typhi bacteria at a dose of 200 ml.